Biofilm Formation by Coagulase-Positive Staphylococcus aureus Isolated from Mozzarella Cheese Elaborated with Buffalo Milk and its Effect on Sensitivity to Sanitizers - Friedriczewski, Anelise Bravo; Gandra, Eliezer Ávila; Conceição, Rita de Cássia dos Santos da; Cereser, Natacha Deboni; Moreira, Lauren Machado; Timm, Cláudio Dias (Acta Scientiae Veterinariae, 2018)
Background: The buffalo milk mozzarella cheese is a new product in the market, with high consumer acceptance and excellent prospects for trade. The cheese is rich in nutrients, which favors the proliferation of microorganisms that can cause food-borne diseases in the consumer. Staphylococcus aureus can cause gastro-enteritis in humans by the production of enterotoxins in food. One problem that may hinder the elimination of undesirable microorganisms in the food industry is the formation of biofilms. The objective of this study was to determine the effect of biofilm formation by Staphylococcus aureus isolated from buffalo mozzarella cheese on sensitivity to sanitizers. Materials, Methods & Results: Fifty samples of buffalo mozzarella cheese were analyzed to investigate the presence of S. aureus. The isolates were obtained through microbiological analysis and identified by PCR. The similarity of the strains was compared through rep-PCR. The distinct strains were tested for biofilm formation in microtiter plates. Soy Tripticase Broth (TSB) was placed in each well of the microtiter plate and overnight cultures of each strain was added. Wells without bacterial culture were used as controls. A villous cap was then placed on the plate and incubated for 48 h at 37°C. During incubation, the biofilms formed on the surface of the villi of the caps. For quantification of biofilm formation, material that remained attached to the cap was stained with crystal violet, the stained biofilm was extracted and the OD570 of each well was measured. Each strain was classified as non-biofilm forming, weak forming, moderately formed or formative strong. Strong forming and non-biofilm forming strains were tested on high density polyethylene, stainless steel and glass surfaces. Plates of 4 cm² of the different materials were placed in TSB where the culture of each isolate was inoculated separately. At each 48 h incubation the plates were washed to remove unbound cells and re-inserted into TSB without the inoculum. After five replicates of the procedure, sterile swabs were passed over the entire surface of each plate for counting in Baird-Parker agar. They were also tested for sensitivity to sodium hypochlorite and iodine after biofilm formation. The biofilm plates were immersed in flasks containing sanitizers, where they remained for 10 min. At the established contact time, the plates were immersed in neutralizing solution for 30 s. After washing with PBS, a sterile swab was passed on the surface of each plate and counts on Baird-Parker agar were performed. The bands profiles obtained on rep-PCR were identical when compared to isolates from the same sample, indicating that each sample was contaminated with only one S. aureus strain. From the twenty S. aureus strain identified, two isolates were classified as strong biofilm formers, seven as moderate formers, ten weak formers and one as non-biofilm builder. The two strong forming strains produced biofilm on the three surfaces tested. The application of sodium hypochlorite and iodine sanitizers promoted a reduction of approximately 2 log bacterial populations on all surfaces of both the biofilm and non-forming strains. Discussion: Most strains of S. aureus isolated from buffalo milk mozzarella cheese have the ability to form biofilm on the surfaces of equipment and utensils that have stainless steel, glass or high density polyethylene components. Although biofilm forming strains are no longer resistant to sanitizers sodium hypochlorite and iodine than non-forming sanitizers, they reach higher concentrations in the biofilm, resulting in larger bacterial populations remaining after application of the sanitizers. These results support the recommendation that the good hygienic practices adopted by industries processing buffalo milk mozzarella cheese should include specific measures to control the Staphylococcus aureus contamination.